Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/978-3-319-02411-0_9
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hypertension in Subarachnoid Hamorrhage: Outcome After Decompressive Craniectomy

Abstract: Intracranial hypertension can occur following aneurysmal subarachnoid haemorrhage (SAH). It can be treated with decompressive craniectomy (DC) with the aim of reducing intracranial pressure, increasing cerebral perfusion and reducing further morbidity and mortality. We studied the outcome of patients undergoing DC following SAH at our institution, to ascertain whether the use of this treatment can be rationalized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…To support our finding, we documented the time at which the highest mean ICP was recorded, which for most patients was within 3 days after SAH; 97.3 % of patients had encountered their highest mean ICP by 5 days post-SAH. In accordance with our results, a recent study indicated that the number of patients with episodes of elevated ICP reached a maximum at day 3 after SAH and decreased only after day 7 [35]. Our findings emphasize the significance of early administration of raised ICP in patients with SAH.…”
Section: Discussionsupporting
confidence: 95%
“…To support our finding, we documented the time at which the highest mean ICP was recorded, which for most patients was within 3 days after SAH; 97.3 % of patients had encountered their highest mean ICP by 5 days post-SAH. In accordance with our results, a recent study indicated that the number of patients with episodes of elevated ICP reached a maximum at day 3 after SAH and decreased only after day 7 [35]. Our findings emphasize the significance of early administration of raised ICP in patients with SAH.…”
Section: Discussionsupporting
confidence: 95%
“…In 2007, Schirmer et al [5] performed surface measurements in 16 SAH patients, but did not find any associations between DC extent and patient outcomes in this small cohort. In another small study of 19 SAH cases based on maximum DC diameter [17], the authors were also unable to identify a link between DC size and SAH outcome. The present study therefore provides the first evidence of the clinical impact of size of DC in the context of SAH using a sufficient sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, less is known about the clinical value of DC size in SAH patients undergoing decompressive surgery. To date, there are only two case series based on surface measurements (n = 16) [5] or maximum DC diameter (n = 19) [17] in SAH patients. These studies, which were limited to very small sample sizes, did not find any associations between DC size and SAH outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, anisocoria and high WFNS grade (WFNS Grade V relative to Grade IV) at presentation were significantly associated with poor outcome. 21,35,45,47 In 1 study, a favorable outcome was more likely in younger patients (< 60 years old). 27 The severity of midline shift, volume of hematoma measured by CT, and delayed surgical treatment were all significantly associated with unfavorable outcome.…”
Section: Predictors Of Outcomes After DCmentioning
confidence: 94%
“…Detailed study parameters and summary statistics from all included studies (with and without a matched control group) that investigated DC in patients with poor-grade aSAH are listed in Tables 2 and 3, respectively. Of the 15 studies included in this review, all of them were observational cohorts (2 prospective, 27,52 13 retrospective 7, 10,21,[24][25][26]28,34,35,39,44,45,47 ). The years of publication ranged from 2002 to 2015, and the reports represented findings from North America (2 studies), Europe (5), and Asia (8).…”
Section: Study Characteristicsmentioning
confidence: 99%